Metabolic enzymes and mixed-function oxygenase (MFO) system in pink snapper (Pagrus auratus): biochemical and histological relationships - Tugiyono (Curtin University, 2001)
The environmental health of aquatic ecosystems depends amongst others, on the chemical pollution coming from activities in the catchment's area. In the Swan River Estuary, Western Australia, the chemical pollutants of concern released into the river are petroleum hydrocarbons and sodium pentachlorophenate (NaPCP). Decreased water quality causes a loss of biotic diversity especially amongst fish populations. The health of aquatic ecosystems can be monitored by fish health, especially fish located at higher levels in the food chain. Pink snapper (Pagrus auratus), an endemic Western Australian fish species, was tested for its potential as a bioindicator of aquatic environmental health. This thesis presents data on the responsiveness of pink snapper to the contaminants of concern, using biomarkers such as serum sorbitol dehydrogenase (SDH), mixed function oxygenase (MFO), metabolic enzymes such as citrate synthase (CS), cytochrome C oxidase (CCO) and lactate dehydrogenase (LDH) and the histological alteration such as hepatic cell lesions (hyperplasia and hypertrophy), and glycogen and lipid droplets. The metabolic enzymes CCO and LDH as well as the hepatic MFO induction and histopathology were proven to be the most suitable biomarkers for use for routine monitoring of the Swan River Estuary using pink snapper as a bioindicator. However, CS activity and hepatic cell lesions (hyperplasia and hypertrophy) did not respond to exposure to contamination and are therefore not suited as biomarkers of effects in pink snapper. The first phase of the study aimed at investigating the responsiveness of juvenile pink snapper to an MFO inducer. Polychlorinated biphenyl isomer # 126 was selected as a model MFO inducer for this study. In the initial experiment, MFO activity was measured as a biomarker of exposure, and serum SDH activity was assessed as a biomarker of liver damage.MFO and SDH activities were of special interest as these biochemical tools have not previously been validated for any Western Australia fish species. Juvenile pink snapper were injected intraperitoneally (i.p.) with 0, 10, 100, 500, 1000 microgram PCB-126 per kilogram. Fish were sacrificed 10 days postinjection, and liver and blood were collected for MFO and SDH analysis, respectively. Doses of 10 and 100 microgram PCB-126 per kilogram caused the highest MFO induction, while doses of 0 and 1000 microgram PCB-126 per kilogram did not result in higher MFO activity relative to carrier-injected (peanut oil) control fish. SDH activities were not significantly different among treatments indicating that hepatocellular damage was not responsible for the reduced MFO activity at the highest dose. Metabolic enzymes in pink snapper exposed by NaPCP were studied in the second phase of the experiment. The aim of this second experiment was to test the responsiveness of pink snapper to contaminants known to cause metabolic perturbations in vertebrates. Juvenile pink snapper were intraperitoneally (i.p.) injected with 0, 5, 10, 20 mg per kilogram. Oxidative enzymes were assessed by measuring CS and CCO activities and glycolytic enzyme was assessed by measuring LDI-1 activity in liver and white muscle tissues. CS activity remained unchanged in both the white muscle and in the liver. CCO activity was significantly enhanced in liver in all treated fish relative to control fish, but not in the white muscle. LDH activity was also higher in liver in all treated fish as compared to control fish, while in white muscle, LDH activity significantly increased at the highest dose injected.The use of a suite of biochemical markers is useful in determining the effects of xenobiotic exposure of aquatic organisms, because it provides a holistic approach with biomarkers at different levels of biological organization. For the third and final phase of the study the suite of biomarkers selected were MFO, metabolic enzyme (CS, CCO and LDH) activities, and histological alternations in combination with physiological indices. The aim of this last experiment was to investigate if a modified liver metabolic activity would alter the MFO induction potential. To test if altered liver metabolism would influence liver detoxication capacities, juvenile pink snapper were i.p. injected with peanut oil (control), or pentachlorobiphenyl # 126 (PCB 126), with sodium pentachlorophenate (NaPCP), or combination of PCB 126+NaPCP. Relative to controls, ethoxyresorufin-O-deethylase (EROD) activity was induced in the PCB 126 and PCB 126+NaPCP fish, but not in the NaPCP group. In the liver, CCO activity was enhanced by the treatments while CS activity remained unchanged and LDH activity was increased in the NaPCP treatment only. In the white muscle, only the PCB 126+ NaPCP treatment enhanced CCO activity, with all other enzymatic activities remaining unchanged. Low serum sorbitol dehydrogenase (sSDH) activity and histopathology of the liver indicated no significant alteration of cellular structure, albeit the lipid droplet size was increased in the PCB 126 and in the PCB 126+NaPCP treatments.It is concluded that the hepatic metabolic changes correspond to histopathological observations, but an altered metabolic capacity does not influence the metabolism of xenobiotics by liver enzymes, as measured by EROD activity. These experiments answered the need to identify a suitable fish species for routine monitoring of the aquatic environment in Western Australia. It also identified the most suitable biochemical markers of exposure and effects, and the suitability of the pink snapper as a bioindicator. Finally, the experiments investigated interactions between biomarkers and provided new knowledge useful to scientists using MFO and/or metabolic enzymes in field or laboratory toxicology.